Draft Genome Sequence of Loktanella maritima Strain YPC211, a Commensal Bacterium of the American Lobster (Homarus americanus) - Ranson, Hilary J. (Genome Announc, 2018)
Loktanella maritima strain YPC211 was isolated from the American lobster (Homarus americanus). We report here the draft genome sequence for L. maritima YPC211 and identify genes of potential importance to its role within the microbial community.